Structural equation modeling of pain management based on rumination mediating resiliency and vitality in women with breast cancer - Givi, Fatemeh; Meschi, Farahnaz; Zhian Bagheri, Masoumeh; Farhood, Dariush (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Pain management in breast cancer patients should be seen what is related to emotion regulation. In patients with emotional problems and anxiety, vitality and resiliency can be good predictors for controlling their negative emotions. This study aimed to explain the pain management model based on rumination mediating vitality and resiliency in women with breast cancer. Methods: The research method was descriptive correlation modeling (structural equations). Participants in this study were women with breast cancer referred to all medical centers (hospitals and private and public clinics) in Tehran, among which 273 were randomly selected. To measure the research variables, rumination response questionnaires, vitality questionnaire, resiliency scale and pain management, and Spearman correlation coefficient test and path analysis, and SPSS.22 and LISREL 8.80 software were used to analyze the data. Results: The results showed that the indirect and direct effect of rumination on pain management by mediating role of vitality was significant (P≤0.05). The indirect and direct effect of rumination on pain management by mediating role of resiliency was significant (P≤0.05). Conclusions: It can be concluded that the pain management model based on rumination with vitality and resiliency mediation in women with breast cancer has sufficient fitness.